2019
DOI: 10.1096/fj.201801794r
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐inducible factor 1α (HIF‐1α) is a major determinant in the enhanced function of muscle‐derived progenitors from MRL/MpJ mice

Abstract: Although the mouse strain Murphy Roths Large (MRL/MpJ) possesses high regenerative potential, the mechanism of tissue regeneration, including skeletal muscle, in MRL/MpJ mice after injury is still unclear. Our previous studies have shown that muscle‐derived stem/progenitor cell (MDSPC) function is significantly enhanced in MRL/MpJ mice when compared with MDSPCs isolated from age‐matched wild‐type (WT) mice. Using mass spectrometry–based proteomic analysis, we identified increased expression of hypoxia‐inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
(80 reference statements)
1
29
0
Order By: Relevance
“…14,15 Increased glycolytic gene expression was also observed in the cultured cells. 14 Using a cardiotoxin injury model, gastrocnemius muscles of MRL mice had reduced macrophage signal intensity and fewer IgG + fibers through 5 days after injury. 15 By 30 days, MRL mice had a greater number of Pax7 + cells per myofiber, and increased dystrophin + muscle fibers.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…14,15 Increased glycolytic gene expression was also observed in the cultured cells. 14 Using a cardiotoxin injury model, gastrocnemius muscles of MRL mice had reduced macrophage signal intensity and fewer IgG + fibers through 5 days after injury. 15 By 30 days, MRL mice had a greater number of Pax7 + cells per myofiber, and increased dystrophin + muscle fibers.…”
Section: Discussionmentioning
confidence: 84%
“…14,15 The elevated levels of HIF1α resulted in several changes in vitro that generally correlate with improved muscle healing in vivo, including increased expression of the myogenic transcription factor Pax7, increased cell proliferation, and an induction of cell survival and reactive oxygen species buffering genes. 14,15 Increased glycolytic gene expression was also observed in the cultured cells. 14 Using a cardiotoxin injury model, gastrocnemius muscles of MRL mice had reduced macrophage signal intensity and fewer IgG + fibers through 5 days after injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It has been reported that the MRL/MpJ mice have accelerated ear punch closure, demonstrating a remarkable capacity for cartilaginous wound closure. 16,17 Previous studies demonstrated that MRL/MpJ mice can heal a full-thickness trochlear groove cartilage injury, whereas C57BL/6J mice do not. It has been found that this strain of mice also exhibits excellent healing in amputated digit tips, 6,7 peripheral nerves, 8 alkali-burned corneas, 9 and cardiac wounds, and also shows enhanced cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%